Using English as a Medium of Instruction in EFL Context in Higher Education - Dahal, Betendra Kumar; Gyawali, Yadu Prasad (Marsyangdi Journal, 2022)
This paper attempts to find out the use of English as a Medium of instruction (EMI) in higher level in English as a foreign language (EFL) classroom. For the study, weselected 16 teachers and 80 students teaching and studying in Bachelor level in Mid-West University and TU affiliated colleges from the Surkhet valley using simple random sampling technique. Then, we distributed the questionnaire to the participants, observed their classes, and took interviews to collect the required information. From the critical analysis and interpretation of the information, we conclude that all the teachers and most of the students in higher level preferred EMI. Similarly, EMI in English subjects forced to implement EMI in other subjects in EFL situation, too. The result showed that EMI is being implemented but majority of the students in higher level have been facing various problems and challenges; specifically, most of the students were interested in learning English through mother tongue though they want to be enclosed with the EMI. This study concludes with suggestion to develop positive attitude towards EMI from practice to policy level with sufficient teaching learning aids, trainings and essential requirements in higher education in EFL context